THE ORGANIZATION OF MADRASAH ALIYAH IN ACEH REFORM ERA - Zainuddin, Zainuddin (State Islamic University North Sumatra, 2020)
Abstract: The Organization of Madrasah Aliyah in Aceh. The main problem in this research is the implementation of madrasa aliyah in the reform era in Aceh. In terms of regulation, Madrasa aliyah in Aceh received an equivalent recognition from schools. Whereas when other regions take a lot of positions to prioritize schools, Aceh with its regulatory power should be able to perform more optimally compared to other regions in the archipelago. Seeing this, it is certainly a challenge for Aceh when it must pay attention to madrassas which in regulations in some regions consider it not their authority. The purpose of this study was to determine the conditions and problems of madrasa aliyah, and their policies and impacts. This research is qualitative research with a responsive evaluation approach. After analysis, it was found that the Aceh government still marginalized the Madrasah Aliyah educational institutions, although several regulations allowed Acehnese to do more. This is of course because the Province of Aceh is a special autonomous region that needs special attention based on the legal principle of lex specialis derogat legi generalis.Keywords: Madrasah Aliyah, special autonomy, policy, Aceh